Multimorbidity's many challenges. Issue 7602 (17th May 2007) - Fortin, Martin; Soubhi, Hassan; Hudon, Catherine; Bayliss, Elizabeth A; Akker, Marjan van den
Abstract : Time to focus on the needs of this vulnerable and growing population